Exploratory Analysis of Cerebral Oxygen Reserves during Sleep Onset in Old and Young Adults - Carlson, Barbara W. (2008)
OBJECTIVE: To explore differences in cerebral oxygen reserves during sleep in old and young adults DESIGN: Descriptive cross-sectional study SETTING: General Clinical Research Center PARTICIPANTS: Nine old (65–84yrs) and 10 young (21–39yrs) adults MEASUREMENTS: Subjects were monitored during the first nightly sleep cycle using standard polysomnography, including measures of arterial oxyhemoglobin saturation (SaO(2)). Changes in regional cerebral oxyhemoglobin saturation (rcSO(2)) were used to estimate cerebral oxygen reserves. General linear models were used to test group differences in the change in SaO(2) and rcSO(2) during sleep. RESULTS: Compared to young subjects, the old had reduced SaO(2), both before sleep (baseline) (F((1,18))=5.1, p=.04) and when asleep (F((1,18))=5.14, p=.04). During sleep, half of the old and none of the young had SaO(2) values below 95%. In addition, the old had more periods of oxygen desaturation (drops in SaO(2)≥4%) (X(2)=24.3, p=.01) and lower SaO(2) levels during desaturation (F((1,18))=11.11, p<.01). Although baseline values were similar, rcSO(2) decreased during sleep by 2.1% in the old (F((1,8))=3.8, p=.05) but increased by 2.1% during sleep in the young (F((1,9))=4.6, p=.04). When the old awakened from sleep, the rcSO(2), but not the SaO(2), returned to baseline; both returned to baseline in the young. CONCLUSION: This exploratory analysis generates the hypothesis that lower SaO(2), combined with declines in regional blood flow, contributes to the decline in cerebral oxygen reserves during sleep in the old. Further study will assess the effects of factors (e.g. medical conditions, subclinical disorders, and sleep architecture) that might account for these differences.